Proceedings of the 16th International Conference on Applied Computing 2019 2019
DOI: 10.33965/ac2019_201912c032
|View full text |Cite
|
Sign up to set email alerts
|

Education in Smart Cities: Practices and Challenges

Abstract: Education is one of the main services offered by the government. Within the advent of smart cities, smart education is defined as the education strategy for smart cities and the concept is becoming more popular with the advent of smart cities. This research aims to address the role of education in smart cities context by providing an overview of the current practices and discussing some of the challenges that exist in delivering education within this context. The following challenges have been identified: advo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As demonstrated in Figure 2, the method of paper selection consisted of using three online databases to collect research articles regarding IoT smart campus adoption and usage. The inclusion and exclusion criteria of the papers are based on the recommendations by [32]. The selection methodology was conducted based on accompanying advances in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated in Figure 2, the method of paper selection consisted of using three online databases to collect research articles regarding IoT smart campus adoption and usage. The inclusion and exclusion criteria of the papers are based on the recommendations by [32]. The selection methodology was conducted based on accompanying advances in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Precisely, Durán-Sánchez et al [31] conducted a systematic review of smart learning, which reported the authors and locations of publications related to smart learning. The work by [32] provides an overview of current educational programs and issues in the smart cities research direction of several recent educational programs and issues in smart cities. Furthermore, the study conducted by Rico-Bautista et al [33] is one of the early works that investigated the role of IoT in smart campuses and smart universities by highlighting the IoT as one of the primary technologies used to implement smart campuses and smart universities.…”
Section: Relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…They used eleven widely used datasets to evaluate various functions of the proposed framework. Reviews on education in smart cities can be found, for example, in the studies of Mehmood et al, 2017a andMolnar, 2019. Many COVID-19-related studies which are utilizing Twitter data have been proposed. Some researchers have explored the thematic analysis of Twitter data.…”
Section: Literature Reviewmentioning
confidence: 99%